(3Led GdMOhO hgi HGdYOO (B134s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3Ydg Ybd WHjYjI GdYbd LhgQ HSjW jOQc GdCTjGA HMbGFbgG GdWHjYjI GHJOGA MQcI hSchf s
(3BNQgG (B:s
(3WdH GdeYGT gh WdH GdEfSGf jWjQ eG JHGYOJ ajg LgGJg Yf eQcRg dHYOgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS hGdYTQhfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs